Human dignity and economic globalisation - Botman, HR (Nederduitse Gereformeerde Teologiese Tydskrif, 2004)
The question addressed here is whether the achievements in the human rights discourses are at stake in the current context of economic globalisation. The answer to this question hinges on the place and role ascribed to governments and states in the global economic context. The outcome of this query is in the social realm where the restoration of human dignity is tested. However, the context of this investigation is both political and economic. Since South Africa has set for itself the political and economic objective to restore the dignity of its humiliated black communities, it remains a pivotal test to the achievement of social gains in a world characterised by economic gains.